Covid-19 and the accelerating smart home. Issue 2 (July 2020) - Maalsen, Sophia; Dowling, Robyn
Home, digital technologies and data are intersecting in new ways as responses to the COVID-19 pandemic emerge. We consider the data practices associated with COVID-19 responses and their implications for housing and home through two overarching themes: the notion of home as a private space, and digital technology and surveillance in the home. We show that although home has never been private, the rapid adoption and acceptance of technologies in the home for quarantine, work and study, enabled by the pandemic, is rescripting privacy. The acceleration of technology adoption and surveillance in the home has implications for privacy and potential discrimination, and should be approached with a critical lens.